W Poznaniu Troczyńskiego. Fragment mapy: uniwersytet - Kobelska, Adela (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
The author proposes to create a map of the city of Poznań which could present the milieu of life activities and practices of Konstanty Troczyński (1906–1942), who was a Polish literary scholar from Poznań. The university is considered as a very important place on this map and remains the main subject of the text. It is seen from a historical and cultural perspective. The author’s attitude is based on the assumption that investigation of modern Polish literary studies history requires both exploring biographies of particular scholars as well as places where new ideas were born.
Troczyński’s Poznań. The University – a fragment of the map